Comparative evaluation of specimen type and processing conditions for studying oyster microbiomes - Almuhaideb, Esam; Hasan, Nur A.; Grim, Christopher; Rashed, Shah Manzur; Parveen, Salina (Frontiers in Microbiology, 2025)
Metagenomic sequencing is increasingly being employed to understand the assemblage and dynamics of the oyster microbiome. Specimen collection and processing steps can impact the resultant microbiome composition and introduce bias. To investigate this systematically, a total of 54 farmed oysters were collected from Chesapeake Bay between May and September 2019. Six different specimen types and processing methods were evaluated for microbial community composition using shotgun metagenomics, namely fresh oyster homogenate (FOH), oyster homogenate after simulated temperature abuse (AOH), Luria broth-enriched oyster homogenate (EOH), dissected stomach homogenate (DSH), hemolymph (HLM), and stomach-gut content (SGC). In general, DSH, EOH, and FOH yielded the highest DNA concentration, while EOH had the highest microbial reads, followed by DSH, HLM, and FOH. HLM produced the highest bacterial species alpha diversity, followed by AOH, EOH, and SGC. Although alpha diversities did not differ significantly, beta-diversity measurements showed significant dissimilarity among methods (p < 0.05) indicating that the specimen types and processing steps do play an important role in representing the composition of the bacterial community. Bacterial species that had the highest log mean abundance included Cyanobium sp. PCC 7001 in FOH, Vibrio vulnificus in AOH, EOH, and DSH, and lastly Synechococcus sp. CB0205 in the DSH, HML, and SGC samples. EOH displayed higher bacterial hits, distinct microbial composition, and higher values of bacterial, phages, and antimicrobial resistance gene reads. Therefore, if studying the overall oyster microbial community, prioritizing optimum specimen collection and processing methods that align with the overall goal of the study is recommended.